Adverse outcomes after surgeries in patients with liver cirrhosis among Korean population: A population-based study - Jo, Hyun Ho; Min, Changwook; Kyoung, Dae-Sung; Park, Min-Ae; Kim, Sang Gyune; Kim, Young Seok; Chang, Young; Jeong, Soung Won; Jang, Jae Young; Lee, Sae Hwan; Kim, Hong Soo; Jun, Baek Gyu; et al. (PloS one, 2021)
We used the Health Insurance Review and Assessment Service-National Inpatient Samples (HIRA-NIS) between 2012 and 2016. In-hospital mortality and hospital stay were analyzed using the data. Mortality rates according to the surgical department were also analyzed. Of the 1,662,887 patients who underwent surgery, 16,174 (1.0%) patients had cirrhosis. The in-hospital mortality (8.0% vs. 1.0%) and postoperative complications such as respiratory (6.0% vs. 5.3%) or infections (2.8% vs. 2.4%) was significantly higher in patients with cirrhosis than in those without cirrhosis. In addition, the total hospitalization period and use of the intensive care unit were significantly higher in patients with liver cirrhosis. In propensity score matching analysis, liver cirrhosis increased the risk of adverse outcome significantly [adjusted OR (aOR) 1.67, 95% CI 1.56-1.79, P<0.001], especially in-hospital mortality. In liver cirrhosis group, presence of decompensation or varices showed significantly increased postoperative complication or mortality. Adverse outcomes in patients with cirrhosis was the highest in patients who underwent otorhinolaryngology surgery (aOR 1.86), followed by neurosurgery (aOR 1.72), thoracic and cardiovascular surgery (aOR 1.56), and plastic surgery (aOR 1.36). The adverse outcomes of patients with cirrhosis is significantly high after surgery, despite advances in cirrhosis treatment.